2019
DOI: 10.3389/fpsyt.2019.00606
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Wellbeing for Children of Parents With Mental Illness: A Model Protocol for Research and Intervention

Abstract: Background: The main objective of this project is to create a research and intervention model to promote large-scale implementation and evaluations of generic very brief interventions for children of parents with mental disorders (COPMI). Feasible interventions for COPMI aged 0–18 years are highly needed, as this is a large high-risk group in society. Reducing behavioral problems and enhancing wellbeing for families with parents affected by any mental disorder are important preventive initiatives. One key prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 47 publications
0
40
0
1
Order By: Relevance
“…Furthermore, having a family member suffering from SMI profoundly affects family dynamics, e.g., by increasing expressed emotions, or by decreasing the patient's ability to support other family members while simultaneously increasing his or her need for their support (8,9). On a converging line, it has been recently confirmed that, for example, preventive interventions targeting the offspring of parents with SMI have tangible prognostic impact both in terms of reduced incidence of mental illness in children and attenuation of internalizing symptoms (10,11). However, within the framework of the early detection of psychosis, a positive family history of psychosis even in combination with a recent drop in functioning was an insufficient predictor of a conversion to first-episode psychosis by itself when compared to symptom-based risk criteria (12)(13)(14).…”
Section: Children Adolescents and Families With Severe Mental Illness: Toward A Comprehensive Early Identification Of Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, having a family member suffering from SMI profoundly affects family dynamics, e.g., by increasing expressed emotions, or by decreasing the patient's ability to support other family members while simultaneously increasing his or her need for their support (8,9). On a converging line, it has been recently confirmed that, for example, preventive interventions targeting the offspring of parents with SMI have tangible prognostic impact both in terms of reduced incidence of mental illness in children and attenuation of internalizing symptoms (10,11). However, within the framework of the early detection of psychosis, a positive family history of psychosis even in combination with a recent drop in functioning was an insufficient predictor of a conversion to first-episode psychosis by itself when compared to symptom-based risk criteria (12)(13)(14).…”
Section: Children Adolescents and Families With Severe Mental Illness: Toward A Comprehensive Early Identification Of Riskmentioning
confidence: 99%
“…Thus, contemporary clinical applied research on the early detection of SMI, even in its most developmentally-oriented branches, typically emphasizes an indicated approach based on subtle psychopathological antecedents (e.g., attenuated positive symptoms and basic symptoms [BS] as included in Clinical High Risk [CHR] criteria, anomalous subjective experiences, and schizotypal traits) (15) while the best strategy to incorporate evidence-based, transgenerational familial risk features still warrants more research (14,16). Therefore, addressing the need of care and developing suitable early identification strategies for familial or genetic high-risk, and other young vulnerable groups is essential (11,(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Children Adolescents and Families With Severe Mental Illness: Toward A Comprehensive Early Identification Of Riskmentioning
confidence: 99%
“…While respectable, such debate seems to elude an obvious medical fact, that is, although not necessarily transitioning to psychosis, UHR helpseekers usually have a lower level of functioning, poorer quality of life, and a higher proclivity for an array of other mental health disorders. On this background it is crucial to highlight the problem of unmet needs and insufficient managing of early signatures of risk of mental illness in offspring of parents with SMI (102).…”
Section: Clinical Translational Implicationsmentioning
confidence: 99%
“…Ireland lags behind most European countries and also Australia, in its lack of legislation and/or a national "think family" policy/practise guidance to support families with PMI (24,26,(33)(34)(35)(36). Moreover, mental health provision in Ireland is severely underfunded when compared with European counterparts, with services operating at between two-thirds to three quarters of recommended staffing levels (37,38).…”
Section: Introductionmentioning
confidence: 99%